Legalitas Peraturan Presiden tentang Sistem Pemerintahan Berbasis Elektronik dalam Sistem Pemerintahan di Indonesia (Legality of the Presidential Regulation on Electronic- Based Government Systems in the Government System in Indonesia) - jumhur, helni mutiarsih; Doly, Denico (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2023)
The Electronic-Based Government System (SPBE) is regulated by a Presidential Regulation. The legal basis for the regulation of SPBE needs to be stronger despite its vital nature. The problem addressed in this paper is the effectiveness of SPBE regulatory laws within the Indonesian government system and the efforts made to enhancethe legality of SPBE regulations within the Indonesian government system. This paper aims to determine the legal effectiveness of SPBE regulations in the Indonesian government system and the efforts to strengthen the legality of SPBE regulations within the system. The method employed in this paper is normative juridical analysis. The discussion shows that the current SPBE arrangements within the Indonesian government system can be considered ineffective. This is due to numerous higher sectoral regulations, which neglect the regulations outlined in the SPBE Presidential Regulation. The legality of regulations concerning SPBE should be elevated to the status of law. Improving the quality of public services across all agencies or institutions necessitates a legal framework that can provide legal certainty. The SPBE rules should, at a minimum, offer a clear and solid definition of SPBE, outline the functions, duties, and authority of central agencies and regional governments, address the formationof the National SPBE Master Plan, and cover aspects such as architecture, roadmap, budget planning, business processes, risk management, infrastructure, information and communication technology audits, organizers, SPBE users, and the granting of SPBE management authority. AbstrakSistem Pemerintahan Berbasis Elektronik (SPBE) diatur dalam Peraturan Presiden (Perpres). Dasar hukum pengaturan SPBE tersebut masih lemah, padahal substansi SPBE sangatlah penting. Permasalahan dalam tulisan ini yaitu bagaimana efektivitas hukum pengaturan SPBE dalam sistem pemerintahan Indonesia dan bagaimana upaya meningkatkan legalitas peraturan SPBE dalam sistem pemerintahan di Indonesia? Tulisan ini bertujuan untuk mengetahui efektivitas hukum pengaturan SPBE dalam sistem pemerintahan Indonesia dan upaya penguatan legalitas pengaturan SPBE dalam sistem. Metode yang digunakan dalam tulisan ini adalah analisis yuridis normatif. Dari pembahasan diketahui bahwapengaturan SPBE dalam sistem pemerintahan Indonesia, saat ini dapat dikatakan tidak efektif. Hal ini dikarenakan masih banyak peraturan sektoral yang lebih tinggi sehingga menyebabkan aturan yang ada dalam Perpres SPBE tidak diindahkan. Legalitas peraturan tentang SPBE perlu ditingkatkan levelnya menjadi Undang-Undang. Peningkatan kualitas pelayanan publik pada seluruh instansi atau lembaga memerlukan legalitas atau aturan yang dapat memberikan kepastian hukum. Aturan SPBE diharapkan paling sedikit mengatur definisi yang jelas dan tegas tentang SPBE; fungsi, tugas, dan kewenangan instansi pusat serta pemerintah daerah; pembentukan Rencana Induk SPBE Nasional; arsitektur, peta rencana, rencana anggaran, proses bisnis, manajemen risiko, infrastruktur, audit teknologi informasi dan komunikasi, penyelenggara, pengguna SPBE; dan pemberian kewenangan pengelolaan SPBE.